Estudo de um sistema supercondutor-ferromagneto: efeitos da aplicação de campo magnético e corrente elétrica - Frota, Diego Araujo (2016)
Using advanced Ginzburg-Landau simulations, we study the superconducting state of a thin super- conducting film under a ferromagnetic layer, separated by an insulating oxide, in applied external magnetic field and electric current. The taken uniaxial ferromagnet is organized into a series of parallel domains with alternating polarization of out-of-plane magnetization, sufficiently strong to induce vortex-antivortex pairs in the underlying superconductor in absence of other magnetic field. We show the organization of such vortex-antivortex matter into rich configurations, some of which are not matching the periodicity of the ferromagnetic film. The variety of possible configurations is enhanced by applied homogeneous magnetic field, where additional vortices in the superconductor may lower the energy of the system by either annihilating the present antivortices under negative ferromagnetic domains, or by lowering their own energy after positioning under positive ferromag- netic domains. As a consequence, both the vortex-antivortex reordering in increasing external field and the evolution of the energy of the system are highly nontrivial. Finally, we reveal the very inter- esting effects of applied dc electric current on the vortex-antivortex configurations, since resulting Lorentzian force has opposite direction for vortices and antivortices, while direction of the applied current with respect to ferromagnetic domains is of crucial importance for the interaction of the applied and the Meissner current, as well as the consequent vortex-antivortex dynamics - both of which are reflected in the anisotropic critical current of the system.